2003
DOI: 10.1562/0031-8655(2003)078<0213:voptbd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Phage T7 Biological Dosimeter by Quantitative Polymerase Chain Reaction Using Short and Long Segments of Phage T7 DNA¶

Abstract: Phage T7 can be used as a biological dosimeter; its reading, the biologically effective dose (BED), is proportional to the inactivation rate |ln (n/n0)|. For the measurement of DNA damage in phage T7 dosimeter, a quantitative polymerase chain reaction (QPCR) methodology has been developed using 555 and 3826 bp fragments of phage T7 DNA. Both optimized reactions are so robust that an equally good amplification was obtained when intact phage T7 was used in the reaction mixture. In the biologically relevant dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
0
28
0
2
Order By: Relevance
“…Alternatively, damage sustained by the proteins could be extended to the RNA in close proximity, causing RNA-protein cross-links or single-strand breaks. A previous study of the protein association of DNA showed that protein-associated DNA is more susceptible to UV damage than isolated DNA (35). UV-induced RNA-protein crosslinking has been described in the scientific literature (22).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, damage sustained by the proteins could be extended to the RNA in close proximity, causing RNA-protein cross-links or single-strand breaks. A previous study of the protein association of DNA showed that protein-associated DNA is more susceptible to UV damage than isolated DNA (35). UV-induced RNA-protein crosslinking has been described in the scientific literature (22).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a 437-base fragment has even been detected up to 350 mJ · cmϪ 2 (24). Several studies have attempted to correlate the degradation of the viral genome to the size of the detected fragment (8,11,23,27,28,29). All published reports on encapsidated poliovirus 1 RNA show that longer fragments (Ͼ800 bases) are at least equal to or more sensitive to UV or oxidation treatment (i.e., ozone, chlorine, chloramines, and chlorine dioxide) than are shorter fragments (Ͻ145 bases) (23,27,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The photoreversion can be added to the protective effect of water ice and various minerals surrounding the microorganisms [39,40] participating in their interplanetary transport. For the protective effect of short UV a further argument is [27]: found in the inactivation action spectrum of B. subtilis HA 101 spores (in the wavelength range 210 nm-290 nm) a decrease of the killing efficiency of the UV radiation at about 230 nm. This effect coincides with our results concerning the photoreversion.…”
Section: Discussionmentioning
confidence: 99%
“…The effects caused by the selected space parameters in the bacteriophage T7 and uracil thin film respectively, have been investigated with several methods: counting the survivor phage particles on infected Escherichia coli B host cells, determination of the UV absorption spectrum and the quantitative characteristics of the spectra [26], quantitative PCR (QPCR), enzymatic digestion, electrophoretic pattern [27,28], in addition, thin layer chromatography (TCL), mass spectroscopy of the photoproducts.…”
Section: Methodsmentioning
confidence: 99%